Synthesis of Side-Chain Oxysterols and their Enantiomers through Cross-Metathesis Reactions of Δ(22) Steroids - Brownholland, David P. (Steroids, 2017)
A synthetic route that utilizes a cross-metathesis reaction with Δ(22) steroids has been developed to prepare sterols with varying C-27 side-chains. Natural sterols containing hydroxyl groups at the 25 and (25R)-26 positions were prepared. Enantiomers of cholesterol and (3β,25R)-26-hydroxycholesterol (27-hydroxycholesterol) trideuterated at C-19 were prepared for future biological studies.